Using the Drosophila Nephrocyte to Model Podocyte Function and Disease - Helmstädter, Martin; Huber, Tobias B.; Hermle, Tobias (Frontiers in Pediatrics, 2017)
Glomerular disorders are a major cause of end-stage renal disease and effective therapies are often lacking. Nephrocytes are considered to be part of the Drosophila excretory system and form slit diaphragms across cellular membrane invaginations. Nehphrocytes have been shown to share functional, morphological and molecular features with podocytes, which form the glomerular filter in vertebrates. Here, we report the progress and the evolving tool-set of this model system. Combining a functional, accessible slit diaphragm with the power of the genetic tool-kit in Drosophila, the nephrocyte has the potential to greatly advance our understanding of the glomerular filtration barrier in health and disease.